PENERAPAN METODE COURSE REVIEW HORAY (CRH)DENGAN MEDIA BENDA KONKRET DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA PADA SISWA KELAS V SDN TANJUNGMERU TAHUN AJARAN 2014/2015 - Susilowati, Ani (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract:Application of Course Review Horay (CRH) Metode with Concret Media in Mathematics Learning Improvement for the 5thGrade Students in SDN Tanjungmeru Academic Year 2014/2015.The objectives of this research are:to describe the steps of the implementation of Course Review Horay method using concrete media,improve the learning of Mathematics about characteristic geometry for fifth grade. This research is a Collaborative Classroom Action Research conducted in three cycles with phases of planning, implementation, observation, and reflection. Subject of the research were all students fifth grade students in SDN Tanjungmeru in academic year 2014/2015 consisting of 25 students. The sources of data were obtained from students, teachers, observers, and document. The data collection technique is to test the results of learning, observation, interview, and documentation.Conclusionof this research areimplementation of Course Review Horay method using concrete media can improve Mathematics learning about characteristic geometryfor the fifth grade students in SDN Tanjungmeru. Keyword: course review horaymetode, concret media, mathematics learning Abstrak: Penerapan Metode Course Review Horay (CRH) dengan Media Benda Konkret dalam Peningkatan Pembelajaran Matematika pada Siswa Kelas V SDN Tanjungmeru Tahun Ajaran 2014/2015.Tujuan penelitian ini adalah mendeskripsikan penerapan langkah-langkah metode Course Review Horay (CRH) dengan media benda konkret, Peningkatan pembelajaran Matematika tentang sifat, jaring-jaring, dan penyelesaian masalah yang berkaitan dengan bangun ruang pada siswa kelas V. Penelitian ini merupakan Penelitian Tindakan Kelas Kolaboratif dilaksanakan dalam 3 siklus dengan tahapan perencanaan, pelaksanaan tindakan, observasi, refleksi.Subjek penelitian ini adalah siswa kelas VSDN Tanjungmeru berjumlah 25 siswa.Teknik pengumpulan data adalah dengan tes hasil belajar, observasi, pedoman wawancara, dan dokumentasi.Kesimpulan penelitian ini adalah penerapan metodeCourse Review Horay (CRH) denganmedia benda konkretdapat meningkatkan pembelajaran Matematika siswa kelas V SDN Tanjungmeru. Kata Kunci: metode course review horay, media benda konkret, pembelajaran Matematika